DETERMINAN EKSISTENSI UMKM DENGAN BANTUAN PEMERINTAH UNTUK USAHA MIKRO SEBAGAI VARIABEL MODERASI (Studi Kasus pada UMKM di Kota Langsa) - Ananda Intan Sari; Dewi Rosa Indah; Nasrul kahfi Lubis (Jurnal Mahasiswa Akuntansi Samudra, 2022)
This research aims to find out the influence of entrepreneurship experience and financial management system on the existence of UMKM with government assistance for micro-businesses as a moderation variable (study on UMKM in Langsa City). The population of this study is the UMKM actors in Langsa City as many as 23,079 UMKM. Sampling techniques using purposive sampling methods as well as in determining samples used slovin formula. Data collection is done by distributing questionnaires to 100 respondents. The data obtained is then analyzed using SPSS (Statistical Package for the Social Science). The research method used is quantitative research and is analyzed using Moderated Regression Analysis (MRA). The results of this study show that the experience of entrepreneurship has a positive and significant effect on the existence of UMKM, financial management systems have a positive and significant effect on the existence of UMKM, government assistance for micro-businesses has a positive and significant effect on the existence of UMKM, government assistance for micro-businesses cannot moderate the influence of entrepreneurship experience positively and significantly on the existence of UMKM, government assistance for micro-businesses can moderate the positive and significant influence of the financial management system on the existence of UMKM, government assistance for micro-businesses can moderate the influence of entrepreneurship experience and financial management system positively and significantly on the existence of UMKM.